2019
DOI: 10.14502/tekstilec2019.62.78-88
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization of PAN/Gelatine Nanofibrous Mats for Cell Growth

Abstract: Nanofi brous mats can be used as a substrate for eukaryotic cell growth in biotechnology, tissue engineering, etc. Several adherent cells (e.g. human fi broblasts) have been shown to grow well on fi ne fi bres. For most applications, it is necessary to sterilize nanofi brous mats before adding the cells. Another possibility would be the addition of antibiotics and antimycotics to the cell culture medium to prevent microbial infection. However, antibiotics are disadvantageous since they might promote the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…While in most applications, the nanofibers used have a very high surface-to-volume ratio, here the increase of the nanofiber diameter is not critical. Earlier investigations of the growth of Chinese hamster ovary (CHO) cells on different nanofiber mats revealed that growing on pure PAN nanofiber mats with their typical thin fiber diameters was impossible, while the cells grew well on PAN/gelatin nanofiber mats [36] with average fiber diameters of 490 ± 130 nm [37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While in most applications, the nanofibers used have a very high surface-to-volume ratio, here the increase of the nanofiber diameter is not critical. Earlier investigations of the growth of Chinese hamster ovary (CHO) cells on different nanofiber mats revealed that growing on pure PAN nanofiber mats with their typical thin fiber diameters was impossible, while the cells grew well on PAN/gelatin nanofiber mats [36] with average fiber diameters of 490 ± 130 nm [37].…”
Section: Resultsmentioning
confidence: 99%
“…This effect may be based on the increased nanofiber diameter, impeding sufficient heat supply to the fiber core. In other thicker nanofibers, like PAN/gelatin or PAN/poly(vinylidene fluoride), this problem may not occur since the blend partners are typically dissolved at temperatures below 500 • C [36,47], while PAN/TiO 2 nanofibers do not show an increased fiber diameter and thus behave similar to pure PAN fibers during carbonization [38]. The same effect of incomplete carbonization under identical conditions was already found for the carbonization of pure PAN nanofibers electrospun with a low voltage of 50 kV, resulting in thicker fibers, where no chemical difference to the usual PAN nanofibers electrospun with 80 kV, as done here, can be expected (to be published).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that carefully optimising the PAN : casein ratio results in straight, relatively thick nanofibres which can be unambiguously stabilised and carbonised, off ering another route to prepare carbon nanofi bres, or desired dimensions and morphology. While this eff ect could also be reached with PAN/ ZnO and PAN/gelatine blends [25,28], the second aim of our study was to fi nd new blends without the cytotoxicity of ZnO to prepare new substrates for tissue engineering or generally cell growth besides PAN/gelatine, which is partly molten during sterilisation by autoclaving at 121 °C [33]. Casein is relatively stable in this temperature range [34] and may thus be an interesting blend for PAN, possibly supporting cell growth similar to gelatine [33] without losing the nanofi brous structure.…”
Section: Introductionmentioning
confidence: 93%
“…While this eff ect could also be reached with PAN/ ZnO and PAN/gelatine blends [25,28], the second aim of our study was to fi nd new blends without the cytotoxicity of ZnO to prepare new substrates for tissue engineering or generally cell growth besides PAN/gelatine, which is partly molten during sterilisation by autoclaving at 121 °C [33]. Casein is relatively stable in this temperature range [34] and may thus be an interesting blend for PAN, possibly supporting cell growth similar to gelatine [33] without losing the nanofi brous structure. Combined with the aforementioned material-related approach, another aim was using suffi ciently mechanically stable carbon nanofi brous mats as conductive substrates for tissue engineering, which has oft en been reported in the literature as advantageous for diverse cell types [35].…”
Section: Introductionmentioning
confidence: 93%